Bureaucrats, Authoritarianism, and Role Conceptions. (June 2021) - O'Connor, Karl; Knox, Colin; Janenova, Saltanat
Governance literature in the developed world is rich with scholarship on the role conceptions of civil servants and how these guide their behavior in the attainment of political objectives set by elected representatives. There is however a dearth of research on the various roles civil servants play in developing countries, specifically those located in authoritarian states. This study uses Q methodology to examine the politician–bureaucrat interface in Kazakhstan, a highly centralized post-Soviet state. It finds evidence of three types of officials: job bureaucrats, policy entrepreneurs, and ethno-politicos. Tribalism and ethno-politics feature as an undercurrent in the political-administrative interface at the senior level. There is an overriding allegiance to the dominant political party that makes neutrality less important as an administrative tenet. Advancement as a career official has little to do with meritocracy, despite the façade, but rather connections are what matter.